Character Education Representation Through Visual Arts At The Tampomas Festival Banjarnegara - Pramisti, Gladis Oky (V-art: Journal of Fine Art, 2025)
Globalization and cultural modernization have weakened the internalization of local character values, particularly among younger generations. This condition highlights the need for contextual and participatory character education rooted in community traditions. The Tampomas Festival in Banjarnegara exemplifies a cultural event in which visual arts serve as a sociological medium, from a symbolic interactionist perspective, for representing character education values and promoting social cohesion through community social practices. These are manifested in stage decorations, costumes, procession attributes, and traditional artworks rich in symbolic meaning. This study examines the role of the visual arts in the Tampomas Festival as a sociological tool for representing values of character education. This research employs a descriptive qualitative approach. Data were collected through field observations during festival preparation and implementation, interviews with local artists, organizers, community leaders, and youth, and visual documentation, including photographs and festival archives. Data analysis involved data reduction, thematic categorization, and interpretive analysis grounded in the sociology of art and symbolic interactionism. The findings reveal that visual art elements at the Tampomas Festival function not only as aesthetic expressions but also as symbolic communication that conveys values such as cooperation, responsibility, religiosity, discipline, and appreciation of local culture. Colors, forms, and traditional motifs are collectively interpreted and contribute to shaping social meaning and cultural identity in Banjarnegara. The study concludes that visual arts within the Tampomas Festival serve as an effective medium for culture-based character education in a non-formal context while strengthening social cohesion through community participation and intergenerational collaboration.